Pengaruh Pencampuran Bahan Bakar Pertalite dengan Bio Etanol terhadap Peforma Mesin Injeksi Yamaha Vixion 150 cc Tahun 2011 - Riva Suro Jatmiko; Kuntang Winangun (TURBO [Tulisan Riset Berbasis Online], 2019)
This study aims to determine the effect of bio ethanol mixing with pertalite fuel on the performance of injection motorcycle engines. By presenting E0-E20 bio ethanol mixture with pertalite fuel. Performance testing parameters are torque, power and specific fuel consumption. In this study using a test method using the dynotest tool to determine the torque and power generated from mixing the fuel. And for testing fuel consumption using the scaffolding of homemade test equipment. The result of this presentation is the right mix presentation for 150cc injection motorbikes, namely the presentation of the E15 mixture of all E15 fuel, the highest torque, power, and stable fuel consumption, not according to the power and torque produced.Keywords: Pertalite, Bio Ethanol, Power, Torque, and Specific Fuel Consumption